Teacher Beliefs on Collaborative Strategic Reading in TOEFL Preparation Course: A Case Study - Ardiana, Fira Khasanah; Putra, Kristian Adi; Drajati, Nur Arifah (JOLLT Journal of Languages and Language Teaching, 2024)
Despite the mandatory inclusion of English in higher education, the limited credit hours and studentsâ€™ varying proficiency levels pose challenges to achieving English language teaching goals. CSR offers a structured approach to enhance reading comprehension through its four stages. While numerous studies have explored CSRâ€™s effectiveness, its application in higher education remains under-researched, particularly for TOEFL preparation. This qualitative study involved three female instructors of a TOEFL preparation course in an Islamic state university which were chosen by convenience sampling. It employs in-depth interviews to examine their beliefs in teaching using CSR for non-English major students in a TOEFL preparation course. The data were analyzed thematically by using deductive coding. The findings revealed that instructors consciously believe in the benefits of CSR for TOEFL preparation. Their beliefs are largely relevant to the theory of CSR, with collaborative learning as a core value and combined with personalized learning to create a positive learning environment that supports students’ reading comprehension and readiness for TOEFL preparation. The result of this can inform instructional strategies and enhance students’ reading comprehension abilities for standardized testing and other assessments, particularly in higher education contexts. Future research may continue to explore the nuances of CSR implementation within a larger scope and more diverse sample to enhance generalizability, or incorporate a mixed-method approach to provide a more holistic view of CSR among educators and students.